2014
DOI: 10.1016/j.jams.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Layer Analysis Method of the Yellow Emperor's Inner Classic in Modern Society

Abstract: This article introduces the Layer Analysis Method of the Yellow Emperor's Inner Classic text to revive its use in modern acupuncture and medicine. This is a crucial concept, especially for the diagnosis and treatment of diseases by acupuncture. First, the rise and decline of this method is explored. Second, the differentiation of this method is described by symptoms, the affected organs, and the stage of the disease. Third, the treatment method is summarized into four categories: (1) equipment, (2) technique, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…In this review, studies investigated the efficacy and mechanism of acupuncture for mild cognitive impairment at different depths using different analytic methods, and they found that deep acupuncture is necessary to achieve significant clinical results (Feng et al, 2012 ; Bai et al, 2013 ; Chen S. et al, 2013 ). Such findings are consistent with the Layer Analysis as described in the Yellow Emperor's Inner Classic (Goh et al, 2014 ). Moreover, the studies consistently showed that deep needling affected a larger number of abnormal brain regions than superficial needling, especially at the hippocampus.…”
Section: Discussionsupporting
confidence: 91%
“…In this review, studies investigated the efficacy and mechanism of acupuncture for mild cognitive impairment at different depths using different analytic methods, and they found that deep acupuncture is necessary to achieve significant clinical results (Feng et al, 2012 ; Bai et al, 2013 ; Chen S. et al, 2013 ). Such findings are consistent with the Layer Analysis as described in the Yellow Emperor's Inner Classic (Goh et al, 2014 ). Moreover, the studies consistently showed that deep needling affected a larger number of abnormal brain regions than superficial needling, especially at the hippocampus.…”
Section: Discussionsupporting
confidence: 91%
“…Others have used ultrasound scans to guide the specific depth for achieving acupuncture sensation [ 4 ]. Such findings correspond to the Layer Analysis as described in the Yellow Emperor's Inner Classic [ 5 ]. Hence, we hypothesize that there could be a relationship between the efficacy of acupuncture treatment and the depth of insertion.…”
Section: Introductionsupporting
confidence: 85%
“…Paradoxically, although acupuncture and the Layer Analysis method [ 5 ] originate from China, the percentage of research indexed in the area of acupuncture depth in Science Direct was ten times as compared to CNKI, the biggest published research database in China ( Figure 5 ). In addition, the search from both databases also points to the lack of research focus on depth generally.…”
Section: Methodsmentioning
confidence: 99%
“…The choice of appropriate acupuncture techniques for different layers is crucial for successful treatment of patients. Needling techniques such as direct subcutaneous needling were primarily used for treating diseases at the skin layer [ 47 ]. Therefore, we used a shallow direct insertion of needles at Bafeng (EX-LE10) and Baxie (EX-UE9) points.…”
Section: Discussionmentioning
confidence: 99%